2009
DOI: 10.1002/jrs.2354
|View full text |Cite
|
Sign up to set email alerts
|

Identification of species formed after pyridine adsorption on iron, cobalt, nickel and silver electrodes by SERS and theoretical calculations

Abstract: The adsorption of pyridine (py) on Fe, Co, Ni and Ag electrodes was studied using surface-enhanced Raman scattering (SERS) to gain insight into the nature of the adsorbed species. The wavenumber values and relative intensities of the SERS bands were compared to the normal Raman spectrum of the chemically prepared transition metal complexes. Raman spectra of model clusters M 4 (py) (four metal atoms bonded to one py moiety) and M 4 (α-pyridil) where M = Ag, Fe, Co or Ni were calculated by density functional the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 48 publications
1
19
0
1
Order By: Relevance
“…Similar results were observed for pyridine adsorbed on iron and cobalt. [61] Hu et al [54] reported pH-dependent SERS spectral changes on silver colloids for some pyridine complexes and assigned the ring breathing modes at 1006, 998 and 998 cm −1 for three different structures of 4-mercaptopyridine surface complex.…”
Section: Surface-enhanced Raman Scattering (Sers)mentioning
confidence: 99%
“…Similar results were observed for pyridine adsorbed on iron and cobalt. [61] Hu et al [54] reported pH-dependent SERS spectral changes on silver colloids for some pyridine complexes and assigned the ring breathing modes at 1006, 998 and 998 cm −1 for three different structures of 4-mercaptopyridine surface complex.…”
Section: Surface-enhanced Raman Scattering (Sers)mentioning
confidence: 99%
“…Yang et al studied the adsorption of 4-mercaptobenzoic acid (4-MBA) on TiO 2 nanoparticles by SERS and UV-vis spectroscopy at different pH values as well as under different temperatures and concentrations. [41] Andrade and Temperini [42] used SERS combined with theoretical calculations to identify molecular species formed after pyridine adsorption on iron, cobalt, nickel, and silver electrodes.…”
Section: Applications Of Sersmentioning
confidence: 99%
“…The bands of the above modes appear in the Py SERS spectrum at approximately 624, 1010, 1035, 1218, and 1598 cm −1 , respectively [12]. For adsorbed pyridine (Py), these frequencies shift significantly with changes of the electrode potential and the electrode material [19][20][21][22]. For example, the experimental results for Py immobilized onto a gas/solid metal interface have shown that the Raman wavenumber of the 1 mode shifts to ∼1003 cm −1 for smooth [23] and to ∼1010 cm −1 for roughened [24] Ag substrates.…”
Section: Introductionmentioning
confidence: 98%